A course-based undergraduate research experience to illustrate the early stages of the drug discovery process - García-Caballero, Melissa; Moya-García, Aurelio Ángel; Torres-Vargas, José Antonio; García-Ponce, Ángel Luis; Rodríguez-Quesada, Ana María (Wiley, 2022)
We have implemented at the University of Málaga (Spain) a new course-based undergraduate research experience (CURE) to involve undergraduate students of Science in a real-world scientific problem. Within the topic “Let's find acetylcholinesterase inhibitors as new drug candidates for the treatment of Alzheimer's”, students have been engaged into the early stages of the drug discovery process. Working in groups of 4–5 persons, they have searched information in databases, proposed solutions to the driving question and designed protocols to carry them out in vitro and in silico. Overall, the implementation of this experience has been very satisfactory in terms of academic performance and students' perception. This article reports a session from the virtual international 2021 IUBMB/ASBMB workshop, “Teaching Science on Big Data”.
Keywords: Medicamentos; Acetylcholinesterase inhibitors; CURE; Drug discovery process